Pelaksanaan Sidang Nikah Dinas Anggota Kepolisian Dalam Mencegah Sex Bebas Pra Nikah: Studi Kasus di Polda Bengkulu, Indonesia - Yusmita Yusmita (Institut Agama Islam Negeri Bengkulu, 2023)
Abstract. One of the objectives of holding a service marriage hearing at the Bengkulu Regional Police is to see whether the marriage is feasible or not or whether the application for a marriage license for a member of the Police is rejected if the marriage session reveals that the character, behavior, and reputation of the prospective husband/wife are not under the established norms (norms). applies in society, for example, having had free sex before marriage or cohabiting, or it is known that the prospective wife is pregnant out of wedlock, and so on. This research is an input for the Bengkulu Regional Police whether marriage trials at the Bengkulu Regional Police are still effective or need new regulations or revisions to existing regulations, to reduce immoral acts among its members, especially premarital sex. Service marriage hearings can indeed prevent or at least reduce free sex among members of the Bengkulu Police, but the rules made by Bid Propam regarding violations by members of the National Police are far more effective in preventing free sex. This is because the rules in Bid Propam have more severe legal sanctions compared to the rules for marriage courts. If found guilty by Bid Propam, free sex offenders can receive severe penalties, namely PTDH (Disrespectfully Dismissed) or PDH (Respectfully Dismissed), delays in promotion, imprisonment, and others. Meanwhile, in Bag Binjah, the punishment is only related to administration, for example, not issuing a marriage license, carrying out coaching, or simply delaying the granting of a marriage license. Keywords: Marriage Trial, Free Sex, Pre-Marriage, Members of the Blood Police Bengkulu